Biosynthesis of nervonic acid and perspectives for its production by microalgae and other microorganisms - Fan, Yong; Meng, Hui-Min; Hu, Guang-Rong; Li, Fu-Li (Applied microbiology and biotechnology, 2018)
Nervonic acid (NA) is a major very long-chain monounsaturated fatty acid found in the white matter of mammalian brains, which plays a critical role in the treatment of psychotic disorders and neurological development. In the nature, NA has been synthesized by a handful plants, fungi, and microalgae. Although the metabolism of fatty acid has been studied for decades, the biosynthesis of NA has yet to be illustrated. Generally, the biosynthesis of NA is considered starting from oleic acid through fatty acid elongation, in which malonyl-CoA and long-chain acyl-CoA are firstly condensed by a rate-limiting enzyme 3-ketoacyl-CoA synthase (KCS). Heterologous expression of kcs gene from high NA producing species in plants and yeast has led to synthesis of NA. Nevertheless, it has also been reported that desaturases in a few plants can catalyze very long-chain saturated fatty acid into NA. This review highlights recent advances in the biosynthesis, the sources, and the biotechnological aspects of NA.